Engaging with society: Organizational communication as social change - Marroquín Velásquez, Lissette (2016)
Processes of development and social change entail organized collective action that materializes in different organizational forms (e.g., a community group, an nonprofit organization, or a special parliamentary commission). Even though an important part of these processes takes place at an organizational and interorganizational level, the field of organizational communication (OC) has only had a minor role to play in this area (Angel, 2013). Although civil society activity suggests the need for further articulation between OC and communication for development and social change (CDSC), these traditions have often been approached as separate fields having little in common.